2010
DOI: 10.1039/b908172k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of alcohols using supported gold and gold–palladium nanoparticles

Abstract: Interplay of theory and computation in chemistryexamples from on-water organic catalysis, enzyme catalysis, and single-molecule fluctuations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 35 publications
9
116
1
1
Order By: Relevance
“…The formation of toluene was also observed with high selectivity in the dehydrogenation of benzyl alcohol over an Au-Pd/TiO 2 catalyst. [36] Our calculation reveals that the disproportionation of benzyl alcohol into benzaldehyde and toluene [Eq. (2)] is thermodynamically feasible [DG…”
Section: Resultsmentioning
confidence: 99%
“…The formation of toluene was also observed with high selectivity in the dehydrogenation of benzyl alcohol over an Au-Pd/TiO 2 catalyst. [36] Our calculation reveals that the disproportionation of benzyl alcohol into benzaldehyde and toluene [Eq. (2)] is thermodynamically feasible [DG…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of pure benzaldehyde was conducted under conditions analogous to those employed in our previous studies of the aerobic benzyl alcohol oxidation 17,29 . Benzaldehyde was oxidized under solvent-less conditions without a catalyst at 353 K in a glass reactor under 1 atm pressure of O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, many researchers have reported the aerobic oxidation of benzyl alcohol to benzaldehyde, using a variety of catalytic systems, including supported metal catalysts, with yields up to B99% [9][10][11][12][13][14] , implying that further oxidation to give benzoic acid does not take place. For example, we recently reported the solvent-less, aerobic oxidation of benzyl alcohol to benzaldehyde using supported gold or gold-palladium nanoparticles as catalysts with a selectivity of 99% to benzaldehyde 6,[15][16][17][18] . These nanoparticlebased catalysts have also been reported for the selective aerobic oxidation of many other alcohols including aliphatic alcohols like 1-octanol with a very high selectivity to octanal 6,19 .…”
mentioning
confidence: 99%
“…The choice of support (carbon versus titania) was also shown to significantly affect both catalytic activity and the distribution of products (selectivity), with carbon-supported materials exhibiting both an increase of activity by a factor of 2, and a lower selectivity to benzaldehyde at isoconversion compared to the analogous TiO 2 -supported catalysts (Table 2). Mechanistic studies were performed for the oxidation of benzyl alcohol using an Au-Pd alloy catalyst synthesised by colloidal method, and it was found that in the absence of oxygen benzyl alcohol was transformed into benzaldehyde and toluene at initial equal rates [29]. The introduction of oxygen significantly increased the rate of benzyl alcohol consumption and benzaldehyde production at the expense of toluene formation.…”
Section: Case I Selective Oxidation Of Alcohols and Polyolsmentioning
confidence: 99%